Genetic Polymorphisms of Alcohol Dehydrogenase and Aldehyde Dehydrogenase: Alcohol Use and Type 2 Diabetes in Japanese Men. (8th June 2010) - Yin, Guang; Ohnaka, Keizo; Morita, Makiko; Tabata, Shinji; Tajima, Osamu; Kono, Suminori
Abstract : This study investigated the association of ADH1B (rs1229984) and ALDH2 (rs671) polymorphisms with glucose tolerance status, as determined by a 75-g oral glucose tolerance test, and effect modification of these polymorphisms on the association between alcohol consumption and glucose intolerance in male officials of the Self-Defense Forces. The study subjects included 1520 men with normal glucose tolerance, 553 with prediabetic condition (impaired fasting glucose and impaired glucose tolerance), and 235 men with type 2 diabetes. There was an evident interaction between alcohol consumption and ADH1B polymorphism in relation to type 2 diabetes (interactionP = .03 ). The ALDH2 4 ∗ 87 Lys allele was associated with a decreased prevalence odds of type 2 diabetes regardless of alcohol consumption. In conclusion, the ADH1B polymorphism modified the association between alcohol consumption and type 2 diabetes. A positive association between alcohol consumption and type 2 diabetes was confounded by ALDH2 polymorphism.